Evaluation of elasto-plastic properties of ITO film using combined nanoindentation and finite element approach. Issue 1 (January 2016) - Gupta, Ankur Kumar; Porwal, Deeksha; Dey, Arjun; Sridhara, N.; Mukhopadhyay, Anoop Kumar; Sharma, Anand Kumar; Barshilia, Harish C.
Abstract: Here we report for the first time the combined nanoindentation experiments and finite element modeling to investigate the in-depth nanomechanical behavior of ~1.25 μm indium tin oxide (ITO) film. The ITO film is grown on silicon substrate by a reactive direct current (DC) magnetron sputtering technique. Here, the contributions of both film and substrate are considered in a power law based nonlinear material model. Based on experimental data a detailed study is carried out in the present work to investigate the stress–strain behavior, the related von-Mises stress and equivalent plastic strain of the ITO film. In addition, the effect of the nanoindentation response of the ITO film on the silicon substrate is also evaluated.